Information system of CO2 emissions - Guzmán-Jiménez, Rosario Marybel (2016)
This article describes the analysis made about the level of carbon dioxide (CO2) emissions mainly generated by domestic electric energy consumption and wastes produced by households. A district zoning was also made through a cluster analysis according to various characteristics of interest. The results of the statistical processing, estimation, projections, data gathering, among others, were shown in an information system specially elaborated for that purpose and in this system thresholds were established as a reference for the generation of warning signals of CO2 high emission levels that were implemented in a digital tachometer inside the information pyramid proposed.